Humanization in the process of academic training of health professionals - Ana Lúcia Assis Simões; Helga Marízia Soares; Joyce Mara Gabriel Duarte; Carolina Feliciana Bracarense; Renata Maciel Cortes (Universidad de Alicante, 2015)
Introduction: Observing effective changes in health practices that are compatible with the new model proposed by SUS, offering a reflection on the processes through which health professionals are formed. Researchers point humanization as one of the guiding themes teaching-learning process. Objective: Identifying, according to the student's opinion, the approach given to the subject of "humanization" during their graduation, and learning their own perceptions upon the subject of "humanization" in healthcare. This is a descriptive, qualitative study. Students participated in the last period of undergraduate courses in Biomedicine, Nursing and Occupational Therapy. The data was collected through the focus group technique, between September and October of 2011. After gathering of the information, the material was submitted to an exploratory reading and, submitted the content analysis of the thematic modality, it was analyzed. Results and Discussion: Two thematic categories emerged: Humanization according to the perception of the students, and Humanization: transversally crossing between theory and practice. The perception of the students seems to be linked to acts like listening to the user, and being empathetic and resolute. Humanization is a theme that would fundamentally contribute to improve healthcare if approached in professional formation.